Gene expression profile of whole blood cells differs in pregnant women with positive screening and negative diagnosis for gestational diabetes - Gelaleti, Rafael B. [UNESP]; Damasceno, Débora C. [UNESP]; Salvadori, Daisy M. F. [UNESP]; Calderon, Iracema M. P. [UNESP]; Costa, Roberto A. A. [UNESP]; Piculo, Fernanda [UNESP]; Martins, David C.; Rudge, Marilza V. C. [UNESP] (BMJ, 2016)
Objective: To evaluate the gene expression profile of whole blood cells in pregnant women without diabetes (with positive screening and negative diagnosis for gestational diabetes mellitus (GDM)) compared with pregnant women with negative screening for GDM. Research design and methods: Pregnant women were recruited in the Diabetes Perinatal Research Centre-Botucatu Medical School-UNESP and Botucatuense Mercy Hospital (UNIMED). Distributed into 2 groups: control (n=8), women with negative screening and non-diabetic (ND, n=13), with positive screening and negative diagnosis of GDM. A peripheral blood sample was collected for glucose, glycated hemoglobin, and microarray gene expression analyses. Results: The evaluation of gene expression profiles showed significant differences between the control group and the ND group, with 22 differentially expressed gene sequences. Gene networks and interaction tables were generated to evaluate the biological processes associated with differentially expressed genes of interest. Conclusions: In the group with positive screening, there is an apparent regulatory balance between the functions of the differentially expressed genes related to the pathogenesis of diabetes and a compensatory attempt to mitigate the possible etiology. These results support the ‘two-step Carpenter-Coustan’ strategy because pregnant women with negative screening do not need to continue on diagnostic investigation of gestational diabetes, thus reducing the cost of healthcare and the medicalization of pregnancy. Although not diabetic, they do have risk factors, and thus attention to these genes is important when considering disease evolution because this pregnant women are a step toward developing diabetes compared with women without these risk factors.